A DESCRIPTIVE STUDY OF MIGRAINE, RESILIENCE, AND QUALITY OF LIFE AMONG FINAL-YEAR MEDICAL STUDENTS IN INDONESIA - Syahrial, Luthfiyyah; Muzar, Zukhrofi (Fakultas Kedokteran Universitas Sriwijaya, 2025)
This study aims to determine the prevalence of migraine and the level of resilience and quality of life in final-year medical students. This descriptive observational study was conducted on final-year medical students of the Faculty of Medicine, University of Muhammadiyah North Sumatra, from November 29, 2023, to December 20, 2023. The results showed that the prevalence of migraine was 16.2%, with 72.4% experiencing mild migraine and 27.6% experiencing severe migraine. Among students with mild migraine, 57% had moderate resilience, and 61.9% reported a good quality of life. Of students with severe migraine, 63% had moderate resilience, and 62.5% reported a good quality of life. These findings indicate that medical students in this study generally have good quality of life and moderate resilience, regardless of migraine severity. This indicates the possibility of adaptive coping mechanisms. However, the small sample size, especially in the severe migraine group (n=8), suggests the need for further research with a larger population to validate these results.